Computational approach for determining the spectrum of DNA damage induced by ionizing radiation. - Nikjoo, H; O'Neill, P; Wilson, W; Goodhead, D (2001)
To study the characteristics of molecular damage induced by ionizing radiation at the DNA level, Monte Carlo track simulation of energetic electrons and ions in liquid water, a canonical model of B-DNA, and a comprehensive classification of DNA damage in terms of the origin and complexity of damage were used to calculate the frequencies of simple and complex strand breaks. A threshold energy of 17.5 eV was used to model the damage by direct energy deposition, and a probability of 0.13 was applied to model the induction of a single-strand break produced in DNA by OH radical reactions. For preliminary estimates, base damage was assumed to be induced by the same direct energy threshold deposition or by the reaction of an OH radical with the base, with a probability of 0.8. Computational data are given on the complexity of damage, including base damage by electrons with energies of 100-4500 eV and ions with energies of 0.3-4.0 MeV/nucleon (59-9 keV microm(-1) protons and 170-55 keV microm(-1) alpha particles). Computational data are presented on the frequencies of single- and double-strand breaks induced as a function of the LET of the particles, and on the relative frequencies of complex single- and double-strand breaks for electrons. The modeling and calculations of strand breaks show that: (1) The yield of strand breaks per unit absorbed dose is nearly constant over a wide range of LET. (2) The majority of DNA damage is of a simple type, but the majority of the simple single-strand breaks are accompanied by at least one base damage. (3) For low-energy electrons, nearly 20-30% of the double-strand breaks are of a complex type by virtue of additional breaks. The proportion of this locally clustered damage increases with LET, reaching about 70% for the highest-LET alpha particles modeled, with the complexity of damage increasing further, to about 90%, when base damage is considered. (4) The extent of damage in the local hit region of the DNA duplex is mostly limited to a length of a few base pairs. (5) The frequency of base damage when no strand breaks are present in the hit segment of DNA varies between 20-40% as a function of LET for protons and alpha particles.